The pilgrim's progress from this world to that which is to come: delivered under the similitude of a dream - Bunyan, John (Published by Jonathan Pounder ... and William W. Woodward ...., 1817)
The life of John Bunyan -- The author's apology -- pt. 1. The pilgrim's progress -- The author's preface to the second part -- pt. 2. The pilgrim's progress -- pt. 3. the pilgrim's progress (generally supposed to be written by another hand).